2002
DOI: 10.1007/s00422-002-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Visuovestibular perception of self-motion modeled as a dynamic optimization process

Abstract: This article describes a computational model for the sensory perception of self-motion, considered as a compromise between sensory information and physical coherence constraints. This compromise is realized by a dynamic optimization process minimizing a set of cost functions. Measure constraints are expressed as quadratic errors between motion estimates and corresponding sensory signals, using internal models of sensor transfer functions. Coherence constraints are expressed as quadratic errors between motion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…However, earlier studies have shown that the absence of physical motion in a driving simulator modifies the driver's reactions [19]. Moreover, computational models of self-motion perception [57] and studies performed on a moving-base driving simulator indicate that driver's control strategies on curved roads make use not only of visual, but also of extra-visual information, such as vestibular (see Box 3) and proprioceptive cues [14,58]. So, on the basis of models proposed in earlier studies [58,59], it has been suggested that these cues are used by the driver to control steering and regulate speed.…”
Section: Influence Of Extra-visual Cues In Steeringmentioning
confidence: 99%
“…However, earlier studies have shown that the absence of physical motion in a driving simulator modifies the driver's reactions [19]. Moreover, computational models of self-motion perception [57] and studies performed on a moving-base driving simulator indicate that driver's control strategies on curved roads make use not only of visual, but also of extra-visual information, such as vestibular (see Box 3) and proprioceptive cues [14,58]. So, on the basis of models proposed in earlier studies [58,59], it has been suggested that these cues are used by the driver to control steering and regulate speed.…”
Section: Influence Of Extra-visual Cues In Steeringmentioning
confidence: 99%
“…It has been known for a long time that the different sensory modalities interact in the perception of self-motion, but how exactly the brain estimates body orientation and self-motion from these cues is still a matter of debate [3,4]. See [5,6] for recent models.…”
Section: Influence Of Visual and Inertial Cues On Self-motion And Selmentioning
confidence: 99%
“…The theoretical approach currently employs two theories: "Sensory Confl ict theory" (SC) and "Subjective Vertical Confl ict theory" (SVC). SC theory is based on the work of Reason and Brand [50,51], expanded by Oman [47,49], who developed the fi nal form of the mathematical description of this theory. Its essence is that all situations that cause motion sickness are determined by the state of the so-called sensory rearrangement [51].…”
Section: Introductionmentioning
confidence: 99%
“…SC theory is based on the work of Reason and Brand [50,51], expanded by Oman [47,49], who developed the fi nal form of the mathematical description of this theory. Its essence is that all situations that cause motion sickness are determined by the state of the so-called sensory rearrangement [51]. In this state there is a sensory confl ict not only between signals from the organ of vision, vestibular organ and other motion sensitive receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation